2013
DOI: 10.1016/j.joca.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Localized 3D analysis of cartilage composition and morphology in small animal models of joint degeneration

Abstract: EPIC-μCT was used to quantitatively assess joint degeneration in two distinct preclinical models. The MMT model showed similar features to human Osteoarthritis (OA), including localized lesion formation and PG loss, while the MIA model displayed extensive cartilage degeneration throughout the joint. EPIC-μCT imaging provides a rapid and quantitative screening tool for preclinical evaluation of OA therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 43 publications
4
71
0
Order By: Relevance
“…Articular cartilage structure and composition were quantitatively evaluated in the tibial plateau as described in our previous study [13]. Scanco evaluation software was used to assess three-dimensional morphological parameters and local attenuation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articular cartilage structure and composition were quantitatively evaluated in the tibial plateau as described in our previous study [13]. Scanco evaluation software was used to assess three-dimensional morphological parameters and local attenuation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have validated this methodology to quantify compositional and structural changes, such as cartilage proteoglycan content, thickness and volume [9,11,12]. Our previous study has characterized the rat MMT model using EPIC-μCT and demonstrated changes in the articular cartilage [13]. These studies have further demonstrated the sensitivity to detect chemically- or mechanically-induced degenerative changes.…”
Section: Introductionmentioning
confidence: 96%
“…Resulting cartilage X-ray attenuation in these scans is inversely related to sGAG content and thereby represent cartilage quality. This technique is suited for quantitative analysis of cartilage degradation for preclinical evaluation of OA [36].…”
Section: Cartilage Evaluation With Contrast Enhanced μCt and Histologymentioning
confidence: 99%
“…Preferential exclusion results in an increase in tissue attenuation inversely proportional to sGAG concentration. It has been successfully applied to the imaging of articular cartilage in mouse and rat femora (8187), cartilage in murine xiphoid (88), caprine osteochondral defects of the talus (89), and more recently, in rabbit intervertebral discs (90). …”
Section: Resultsmentioning
confidence: 99%